An Objective Pain Score for Chronic Pain Clinic Patients - Agnes K. Pace; Melanio Bruceta; John Donovan; Sonia J. Vaida; Jill M. Eckert (Pain Research and Management)
Objectives. Although numerous studies have looked at the numeric rating scale (NRS) in chronic pain patients and several studies have evaluated objective pain scales, no known studies have assessed an objective pain scale for use in the evaluation of adult chronic pain patients in the outpatient setting. Subjective scales require patients to convert a subjective feeling into a quantitative number. Meanwhile, objective pain scales utilize, for the most part, the patient’s behavioral component as observed by the provider in addition to the patient’s subjective perception of pain. This study aims to examine the reliability and validity of an objective Chronic Pain Behavioral Pain Scale for Adults (CBPS) as compared to the traditional NRS. Methods. In this cross-sectional study, patients were assessed before and after an interventional pain procedure by a researcher and a nurse using the CBPS and the NRS. Interrater reliability, concurrent validity, and construct validity were analyzed. Results. Interrater reliability revealed a fair-good agreement between the nurse’s and researcher’s CBPS scores, weighted kappa values of 0.59 and 0.65, preprocedure and postprocedure, respectively. Concurrent validity showed low positive correlation for the preprocedure measurements, 0.34 (95% CI 0.16–0.50) and 0.47 (95% CI 0.31–0.61), and moderate positive correlation for the postprocedure measurements, 0.68 (95% CI 0.56–0.77) and 0.67 (95% CI 0.55–0.77), for the nurses and researchers, respectively. Construct validity demonstrated an equally average significant reduction in pain from preprocedure to postprocedure, CBPS and NRS median (IQR) scores preprocedure (4 (2–6) and 6 (4–8)) and postprocedure (1 (0–2) and 3 (0–5)), p<0.001. Discussion. The CBPS has been shown to have interrater reliability, concurrent validity, and construct validity. However, further testing is needed to show its potential benefits over other pain scales and its effectiveness in treating patients with chronic pain over a long-term. This study was registered with ClinicalTrial.gov with National Clinical Trial Number NCT02882971.